LIGNIN AND FATTY ACID RECORDS IN LAKE BAIKAL SEDIMENTS OVER THE LAST 130 KYR: A COMPARISON WITH POLLEN RECORDS - Ishiwatari R.; Shinoyama S.; Yamamoto S. (My University, 2006)
A 10 m sediment core from Academician Ridge in Lake Baikal was analyzed for its molecular composition using on-line TMAH (tetramethylammomium hydroxide) thermochemolysis. Major products are lignin phenols, n-C14 to C30 fatty acids (alkanoic acids), cutin acids, hydroxy acids and aliphatic dicarboxylic acids. Lignin phenols are abundant in warmer periods (the interglacial: marine isotope stage (MIS) 5e and MIS 1), but extremely low in the other (colder) periods. This result coincides well with pollen records reported for a core near the present site, where an expansion of coniferous forests in sub-stage 5e and MIS 1 was implied. Normal C24–C30 alkanoic acids, important components of plant wax esters, are abundant in 5e and MIS 1 and are present in significant amounts in the other (colder) periods, unlike the lignin phenols. A high abundance of n-C24 to C30 alkanoic acids relative to lignin phenols in the Bølling–Allerød warm period suggests an enhanced development of herbs.It is implied from comparison of the sedimentary lignin phenol record with fossil pollen records and lignin phenol analysis of modern pollen that the ratio of cinnamyl phenols to vanillyl phenols may serve as an indicator of pollen contribution to sedimentary organic matter.